Oligarquia e elites políticas no Espírito Santo: a configuração da liderança de Moniz Freire - Quintão, Leandro do Carmo (2016)
In order to analyze the setting of the leadership of Moniz Freire during the First Republic, one used the period between 1881 and 1918, to understand the way he related to the political elite from Espirito Santo, through the “Partido Republicano Construtor”, which he headed. One works the hypothesis that he used the oligarchic leadership on his political group, with characteristics of charismatic domination, built upon symbolic power, created in the early years of his political activities, concerning heroic and notorious types of political capitals. Moniz Freire reached this stage by his notorious intelligence and efforts for defending a plan for regional establishment of Espirito Santo, becoming its main spokesman. Such power has survived the political changes that occurred in Brazil and in Espirito Santo, such as the change of the regime and the political/party reorganization. Such changes, which happened in a short period of time, resulted in a crisis of legitimacy, in which Moniz Freire emerged as type of Savior. Considering the context and favorable political conditions, he ruled the State from 1892 to 1896, starting the implementation of the plan for regional establishment, as argued in the past, which, connected to good expectations for financial development of the state, highlighted his political capital, specially his heroic one, and his total control over the oligarchy that formed the “Partido Republicano Construtor”. Some years later, he was once again considered a savior, when facing the crisis of legitimacy within the oligarchy, when he was re-elected as the main governor of the State in 1900. Then, his political failure started, with a symbolic decline, when he was no longer able to solve the financial problems of the state and the political problems within the oligarchy. His charismatic authority, undermined, led to political decline, with the insubordination of his successor in the state government in 1905. The symbolic and political decay merged, leading him to collapse and his oligarchy to dissolution. This study is based in concepts such as “domination” and “charisma” from Max Weber; “symbolic power” and “political capital” from Pierre Bourdieu; “savior” and “legitimacy crisis” from Raoul Girardet. One also deals with the notion of “social representations” and the scheme of “appropriation-representation-circulation” from Roger Chartier. Magazines and newspapers – neutral, allies and opponents of Moniz Freire – as well as official documents and bibliography from that period support the proposed hypothesis. One uses content analysis, in order to investigate social representations of allies, and rhetoric, as a key for reading and understanding the construction of texts, mainly the ones from Moniz Freire, as a strategy for convincing, in the beginning of his political career